Biscarbamate cross-linked polyethylenimine derivative with low molecular weight, low cytotoxicity, and high efficiency for gene delivery - Yuan WE (Dove Medical Press, 2012)
Yu-Qiang Wang1,*, Jing Su2,*, Fei Wu2, Ping Lu1, Li-Fen Yuan1, Wei-En Yuan2, Jing Sheng1, Tuo Jin21Department of Geriatrics, Shanghai Ninth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China, 2School of Pharmacy, Shanghai Jiao Tong University, Shanghai, People’s Republic of China*Both authors contributed equally to this workAbstract: Polyethylenimine (PEI), especially PEI 25 kDa, has been widely studied for delivery of nucleic acid drugs both in vitro and in vivo. However, it lacks degradable linkages and is too toxic for therapeutic applications. Hence, low-molecular-weight PEI has been explored as an alternative to PEI 25 kDa. To reduce cytotoxicity and increase transfection efficiency, we designed and synthesized a novel small-molecular-weight PEI derivative (PEI-Et, Mn: 1220, Mw: 2895) with ethylene biscarbamate linkages. PEI-Et carried the ability to condense plasmid DNA (pDNA) into nanoparticles. Gel retardation assay showed complete condensation of pDNA at w/w ratios that exceeded three. The particle size of polymer/pDNA complexes was between 130 nm and 180 nm and zeta potential was 5–10 mV, which were appropriate for cell endocytosis. The morphology of PEI-Et/pDNA complexes observed by atomic force microscopy (AFM) was spherically shaped with diameters of 110–190 nm. The transfection efficiency of polymer/pDNA complexes as determined with the luciferase activity assay as well as fluorescence-activated cell-sorting analysis (FACS) was higher than commercially available PEI 25 kDa and Lipofectamine 2000 in various cell lines. Also, the polymer exhibited significantly lower cytotoxicity compared to PEI 25 kDa at the same concentration in three cell lines. Therefore, our results indicated that the PEI-Et would be a promising candidate for safe and efficient gene delivery in gene therapy.Keywords: gene delivery, polyethylenimine, nanoparticles, cytotoxicity, transfection efficiency